Polacy w niemieckiej policji pomocniczej. Schutzmannschaftsbataillon 202 w świetle zeznań jego członków - Wenklar, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Schutzmannschaftsbataillon 202, the unit of the German auxiliary police, was formed at the turn of 1942. Polish volunteers, who positively responded to the announcement published in the Polish-language press concerning recruitment to the so-called navy-blue police Polnische Polizei, were enlisted into it. From June 1942 they were trained in the area of the Waffen SS camp in Pustkow. Originally they were informed that they would serve in the precincts of the navy-blue police located in the General Government. The unit was staffed with Polish officers and non-commissioned officers but at the same time there were also German supervising officers. Overall, over 400 people participated in the training in Pustkow. After the conclusion of training, the policemen were enrolled into the German auxiliary police as the Schutzmannschaftsbataillon 202. The command was assumed by the Germans. Battalion 202 was originally used in the background of the German Army Group “Middle” on the Eastern Front. However, after a series of desertions and attempts to find contact with Soviet partisans, the unit was transferred to Volyn. Once there, the policemen were protecting Polish groups against exterminatory actions undertaken by the Ukrainian Insurgent Army UPA and also taking part in retaliatory strikes which simply meant the pacification of Ukrainian villages. It is worth noting that the unit often found itself in conflict with Ukrainian policemen of Schutzmannschaft. Many of the above-mentioned activities were performed with indifference, ignorance or even disapproval of the unit’s German supervisors. In Volyn further desertions took place; many ex-policemen joined the Home Army AK. In January 1944, in the face of approaching war front, the battalion which had lost the trust of the German side, was transferred to Lvov and after that, in February of the same year, to the village of Drusenheim in Alsace. After three months long stay in the backlines of the Western Front, the unit was disbanded; the policemen were transported to the General Government and separately inducted to the precincts of gendarmerie. After the Second World War the individual policemen from the Battalion 202 were prosecuted for collaborating with Germany. They were also invigilated by the Security Office UB. The testimonies and pronouncements gathered by the UB permit us to reconstruct the history of this collaborative unit to a large degree.
Keywords: Polacy; policja pomocnicza; Niemcy; II wojna światowa; Schutzmannschaftsbataillon 202